Korelasi Genetik Antara Bobot Sapih dengan Bobot Satu Tahun dan Laju Pertumbuhan Pasca Sapih Sapi Brahman Cross - Gushairiyanto, Gushairiyanto; Depison, Depison (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
IncreasedÂ productionÂ ofÂ meatÂ hasÂ toÂ beÂ doneÂ toÂ meetÂ theÂ needsÂ ofÂ theÂ animalÂ proteinÂ demand continuesÂ toÂ increase,Â thisÂ studyÂ aimsÂ toÂ lookÂ atÂ theÂ possibilityÂ ofÂ acceleratingÂ theÂ implementationÂ of selection with respect to the production of meat that is when the cow weaned in order to improve respos selection.Â ThisÂ studyÂ collectedÂ dataÂ includesÂ birthÂ weight,Â weaningÂ weight,Â weightÂ ofÂ oneÂ yearÂ andÂ post- weaning growth rate and identify the lineage of every cow that became the object of research. The study was conducted by analyzing the data to obtain heritability value weaning weight, weight of one year and post-weaning growth rate and the value of genetic correlation between cow weight and weight one year post-weaning growth rate.Â The results showed heritability values weaning weight, weight of one year and post-weaning growth rateÂ includeÂ highÂ category,Â respectivelyÂ wereÂ 0.62 Â±Â 0.40,Â 1.05Â Â±Â 0.59Â andÂ 1.25Â Â±Â 0.63.Â TheÂ valueÂ of genetic correlation between weaning weight and weight one year post-weaning growth rate was positive and included high category, each is 0.51 and 0.55. This means that selection on weaning weight increase willÂ beÂ followedÂ alsoÂ byÂ theÂ increasingÂ weightÂ ofÂ oneÂ yearÂ andÂ post-weaningÂ growthÂ rate,Â selectionÂ on weaningÂ weightÂ willÂ accelerateÂ theÂ implementationÂ ofÂ selectionÂ ofÂ theÂ parametersÂ relatedÂ toÂ meat production, so as to increase the selection response per year.